The Role of the Constitutional Court in Realizing Dignified Justice: A Constitutional Law Perspective - Latif, Abdul; Sangga, Amin; Thahir; Suaib; Jalil (Faculty of Law, Universitas Pekalongan, 2024)
This research is a normative legal study with a conceptual and legislative approach. The research results show that the role of the Constitutional Court in Indonesia in realizing dignified justice can be carried out by using the theory of dignified justice in the efforts of the Constitutional Court judges to interpret the constitution. The efforts of the Constitutional Court judges to interpret the constitution based on dignified justice are aimed at ensuring that substantive justice can be realized for the community. The role and orientation of the Constitutional Court's authority from the perspective of constitutional law can be seen in the efforts of the Constitutional Court judges to optimize the Court's authority through constitutional interpretation. In this context, both judicial restraint and judicial activism play important roles in the development of law and the enforcement of justice, and their application often depends on the specific context of each case